Contribution of Fishery Production and Marketing Sector in the Household Food Security in the Red Sea State, Sudan - Hamza, Mohamed; Alhasseen, Imad; Mohamed, Salah (American Scientific Research Journal for Engineering, Technology, and Sciences, 2017)
This study aimed to determine the contribution of fishery production and marketing sector in the household food security in the Red Sea State, Sudan. The study used questionnaire, field survey and personal communications as primary sources of data collection; literature from previous studies and records were used as secondary sources of data. The population of fishery production and marketing sectors were identified as fishers, fish sellers, labors, restaurant owners, fish exporters, fishery input producers, and traditional fish product producers, representing 41.9%, 14%, 25.9%, 10%, 1.7%, 4% and 2.7% of the sampled population, respectively. Participation of women in fishery production and marketing activities of the sampled population constitute 4.7%.The average annual fish production was calculated as 769.97 tons from the daily fish landing in Feb. 2015 and was estimated as 1436 tons through questionnaire results. The results indicated that 99% of fin fish production is sold in Port Sudan and Swakin localities. The results showed that 85.4% of the enterprises are managed by their owners while 8.5% hire their relatives with 85% of enterprises in fishery sector were depends on self-financing. The recently developed central fish market and specialized sea food restaurants center represent a positive impact on fisheries production and marketing.